2022
DOI: 10.14710/ijred.2022.45799
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation of a New Modified Savonius Wind Turbines

Abstract: The classic Savonius semi-circular blade turbine has a relatively low power coefficient.The performance of a Savonius wind turbine depends on its geometrical parameters. Various blade profiles have been developed in the past years to improve the performance of this class of turbine. In this paper, a new blade shapes of Savonius wind turbine is investigated numerically by using the CFD method , by using transient conditions and set k omega turbulence model.The new blade has different concave and convex shape, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…Wind power is captured by wind turbines and converting it to electricity. Wind power is the fastest-growing energy sector in the world because of its many advantages, such as unlimited, free, renewable resources, economic value, maintenance cost, and placement of wind harvesting facilities [9]. Unlike traditional power plants, harvesting wind power is a clean, non-polluting way to generate electricity and emits no greenhouse gases.…”
Section: Wind Energymentioning
confidence: 99%
“…Wind power is captured by wind turbines and converting it to electricity. Wind power is the fastest-growing energy sector in the world because of its many advantages, such as unlimited, free, renewable resources, economic value, maintenance cost, and placement of wind harvesting facilities [9]. Unlike traditional power plants, harvesting wind power is a clean, non-polluting way to generate electricity and emits no greenhouse gases.…”
Section: Wind Energymentioning
confidence: 99%
“…Likewise, a number of researchers have made contributions through their experimental research 16 . M. Zemamou et al, 18 reported their investigation focused at improving the Cp of Savonious rotor, while Arifin Sanusi et al, 17 investigated combination of the circle-shaped with a concave elliptical model to improve the performance. In two new possible areas, namely far offshore and in urban and rural settings, VAWT has recently experienced resurgence in demand for wind energy harvesting.…”
Section: Background and Literature Reviewmentioning
confidence: 99%